Entrepreneurial marketing strategy on tempe sanan chips small and medium entreprises in Malang - Novi Haryati; Moch. Adi Surahman; Miftakhurrizal Kurniawan; Faizatul Amalia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
The development of national industry in Indonesia still faces a number of obstacles such as inadequate infrastructure condition, as well as an increase on subsidised fuel price increase, basic electricity rate and minimum wage. Small and medium scale (SME) food industry is one sector of creative industries with a high contribution to the Indonesian economic development. This study aims to get an overview related to agribased agri-sector SME and to identify internal and external factors to formulate appropriate strategies. The data used were primary data from 30 craftsmen in tempe Sanan Malang Chips Center. Data analysis was done descriptively quantitative using Entrepreneurial Marketing concept consisting of 7 dimensions. The results showed that the SME had a strength in terms of its already known products, the weakness was that the product has not been able to meet the export market share. An appropriate strategy was to improve marketing and processing technology.